Inventory of birds in the Peruvian Amazon: Case of lake Cuipari - Seijas-Díaz, José; Martell, Karla; Schrader, Juan; Navas-Vásquez, Manuel; Barbachán-Ruales, Enrique; Cabel-Rabines, Jessica (Acta Scientiarum. Biological Sciences, 2025)
The study conducted at Lake Cuipari, located in Loreto, Peru, focused on the rich avifauna biodiversity of this Amazonian ecosystem, highlighting its significance for conservation and ecotourism. This study aimed to inventory bird species and assess the ecotourism potential of the area. Using visual and auditory census methods within a 4 km radius around the lake, invasive techniques were avoided to minimize the impact on the birds. Species were identified using high-resolution equipment, such as binoculars and audio recording devices, as well as through vocalization analysis. Field guides and taxonomic classifications were consulted to corroborate the identification. The results revealed a diversity of 110 bird species distributed across 23 orders and 43 families, including both native and migratory species. The conclusions of this study highlight the importance of Lake Cuipari as a significant area for avian conservation, particularly because of the presence of species classified as vulnerable (VU). While the lake currently supports diverse avifauna, the potential for latent threats, such as habitat degradation or human activities, underscores the need for proactive conservation measures. In addition, its ecological richness presents an opportunity to promote ecotourism in a sustainable manner. These findings emphasize the potential of birdwatching and biodiversity valorization to contribute to both ecosystem conservation and community well-being. Although this study provides valuable baseline data on avian diversity, further research and integrated management efforts are necessary to fully address the balance between conservation and local economic development. Such efforts should consider broader ecological and socioeconomic factors to support a more comprehensive approach to sustainable management.